Evaluación del tiempo termal óptimo en mezcla forrajera para bovinos pastoreados en la hacienda alelí canton Pillaro. - Moreno Chávez, Johana Patricia (2020)
The present research work was carried out in Tungurahua province, Santiago de Pillaro Canton, “Alelí” Farm with the objective of evaluating the optimal thermal time in a fodder with the purpose of determining the amount of accumulated temperature in relation to the NDF of the grasses for regrowth to have a constant quality, determine the cost-benefit and evaluate the body condition of the animals thus determining the viability of the research for which bromatological and laboratory examinations were carried out. The field study was carried out at Alelí Farm , and it began by placing 2 thermometers of high and low temperatures in a determined paddock, which recorded the information of the temperatures 6 am and 6 pm during the time that the investigation lasted, started. On day 0 (November 24, 2019), the first sample was taken and sent to the laboratory for bromatological analysis, obtaining an FDN of 47.38, the following sample of the fooder mixture was sent 15 days after the re-growth (day 8-Dec-2019) for another bromatological analysis obtaining a FDN of 32.00 with a thermal sum of 92.25 ° C and it was culminated with the collection and then the third sample was sent to the next 5 days (13-Dec- 2019) for analysis with a FDN of 34.00 with a thermal sum of 122 ° C. For this research work 15 cows were used.5 in the first third of lactation, 5 in the second third of lactation, and 5 in the third of lactation,. Weights were taken from them, a record of daily milk production was kept, and blood samples were also taken and sent to the BUN and in urine for ketone body analysis With the new grazing management, production increased from 16.39 lts / day to 19 lts / day in average cow / day.